An analogous study of Leo Tolstoy and Fyodor Dostoevky with their perceptions of reality : revisiting Tolstoy and Dostoevsky - Iqbal, Arsheel (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2015